Peningkatan Hasil Belajar dalam Menyelesaikan Persoalan Geometri Melalui Penerapan Media Visual GeoGebra - I Komang Wahyu Wiguna (Edukasi: Jurnal Pendidikan Dasar, 2020)
The purpose of this research is to improve students' mathematics learning outcomes who are below the standard B grade (good ≥ 70), especially in geometry solving problems through the application of Geogebra visual media. This research is a Classroom Action Research which is conducted in two cycles with 18 students of A2 third semester as subjects and an observer. Each cycle includes planning, implementing actions, observing and reflecting. The success of this research if at least 75% of students get a value of ≥ 70. The results show that the minimum standard value of students in the first cycle is 16.67% with an average value of 60.89 and in the second cycle it is 77.78% with an average value is 70.11. The conclusion of this research is that Geogebra visual media can improve mathematics learning outcomes of A2 third Semester students of PGSD STAHN Mpu Kuturan Singaraja Keywords: learning outcomes, GeoGebra, geometry